Brachyuran crab diversity and abundance in different aged stands in the Matang Mangrove Forest Reserve, Perak, Malaysia - Ibrahim, Siti Aminah (2019)
The Matang Mangrove Forest Reserve (MMFR) has been sustainably managed since 1902, and is currently harvested mainly for charcoal production and for poles used in the construction industry. It is also rich in aquatic animals like fish, crabs, prawns (water bodies) and mudskippers, molluscs and crabs (intertidal shore). Crab abundance appears to be related to the diversity of the mangrove vegetation aged. It is hypothesized that crab abundance is low in the area of young vegetation stands compared to older vegetation stands in MMFR due to the difference in vegetation diversity and stand structures. Two species, Rhizophora apiculata and Rhizophora mucronata dominated the young aged stands due to the management practise of replantation. In the older aged stands, which was left for natural growth for more than 30 years, there are five (5) species recorded which are R. apiculata, R. mucronata, Bruguiera parviflora, Excoecaria agallocha and B. gymnorhiza. The objective of this study was to examine the composition, diversity and abundance of mangrove crabs in different aged forests stands in MMFR. 20 plots of size 10m X 10m each were set up distributed along four (4) transects at three (3) different aged stands. Each transect has five plots set up. Vegetation parameters such as tree species, diameter at breast height (DBH), height and the above ground biomass within each plot were measured. Buried pitfall traps were used to collect the crab samples. Five (5) pitfalls traps were buried in each plot sampling area and left overnight before collection. Eight (8) species of mangrove crabs, Perisesarma eumolpe, Perisesarma onychophorum, Episesarma versicolor, Episesarma singaporiensis, Episesarma mederi, Uca rosea, Sarmatium crassum and Clistocoeloma merguiense, of mangrove crabs were successfully collected and identified from a total of 215 individuals. The highest abundance of crabs was found in the young and middle-aged stands, which were below 30 years. The environmental conditions provided by the young and middle-aged stands may have influenced the crab diversity and abundance. Transect one (1) which was planted with Rhizophora apiculata aged below 20 years showed the highest composition of mangrove crabs in this study. This was followed by the middle-aged vegetation stands, aged more than 20 years but below 30 years, in Transect two (2) and three (3) planted with Rhizophora mucronata and Rhizophora apiculata, respectively. These studies also successfully found mud-dweller crab, Uca rosea with four (4) individuals caught from transect one. This species is normally found near the riverbank of mangrove forest. The results strongly suggest that the forest management practices are able to facilitate and sustain the composition of mangrove crabs.